Features of teaching supplements designed to help primary teachers reduce student misconceptions in mathematics - Endah Budi Rahaju; Dwi Iriyani; Ahmad Wachidul Kohar (Universitas Hamzanwadi, 2023)
The findings of teacher misconceptions of mathematics at various levels indicate a wide variation of mathematics taught to students. This research aims to produce valid, practical, and effective teaching supplementary materials for integers, fractions, two dimensional and three-dimensional shapes that can overcome misconceptions. This two-year development research applied Plomp's development phases: preliminary investigation, design, realization, test phase, evaluation, and revision. The data were analyzed from teacher misconceptions about mathematics from the first year of the study, the development of teaching material supplements, the results of observations on the implementation of teaching materials, the teacher's response questionnaire to the implementation of the teaching materials, and test results. The research subjects were primary school teachers in Sidoarjo who experienced mathematical misconceptions. The results showed that the teaching material supplements developed met valid, practical, and effective criteria based on expert validation, teacher responses, and teacher work results on the assessment sheets. The features of the supplements were developed based on cognitive conflict and the resolution of conflicting perspectives and the teachers' existing ideas and extend them, through, for example, the analogy to a new domain, where those are presented in either the materials or the assessments.